IMPLEMENTATION AND ASSOCIATION OF THE CIRCULAR ECONOMY IN THE MANAGEMENT OF SOLID WASTES IN RESENDE: STUDY OF MUNICIPAL PRACTICES SEEKING INTEGRATION BETWEEN PROCESSES OF SELECTIVE COLLECTION AND CIRCULARITY: Study Of Municipal Practices Seeking Integration Between Processes Of Selective Collection And Circularity - Ribeiro, Anderson De Oliveira; da Silva, Raiane Teodoro (Episteme Transversalis, 2024)
The unregulated extraction, too much linear production and excess waste disposed of in the environment cause various damages both in the present and in the future of the population and directly affects its quality of life. This article aims to define and expose circular ideas, its thesis, applications, defend its importance, in addition to aligning these points with a possible implementation of the theme in the municipality of Resende/RJ - a city with about 132.3 thousand inhabitants, potential productive capacity and generates numerous wastes, requiring a proper management of these. The solutions available through the circular economy brings options for reuse and reintegration of this wastes and seeks ways to assist the process, either in the promotion of circular actions or mass awareness of the population on a subject of extreme importance and necessary to the environment.